Periprosthetic fracture morphology of a femoral neck prosthesis: an in vitro study - Tsitlakidis, Stefanos; Westhauser, Fabian; Jäger, Sebastian; Klotz, Matthias C. M. (Proceedings of the Institution of Mechanical Engineers. Part H, Journal of engineering in medicine, 2019)
Femoral neck prostheses have been developed for the treatment of osteoarthritis in young and active patients. The concept combines a bone-conserving and minimal invasive technique with proximal load transferring by metaphyseal anchoring, which results in a more physiological loading pattern. However, little is known about the morphology of periprosthetic fractures. Thus, the aim of this study was to describe fracture patterns and to determine patient-specific factors favoring periprosthetic fracture. This study was performed as a biomechanical experimental study using 10 fresh frozen femora and 10 Silent-Hip femoral neck implants (DePuy International Ltd., Leeds, UK). In order to simulate physiological loading, a static muscle reconstruction (abductor muscles and iliotibial band) and a dynamic simulation of the gait cycle were applied. During biomechanical testing (50% and 100% of normal weight-bearing), three periprosthetic fractures with two different morphologies occurred. The first pattern corresponds to an abrupt breakaway. The second type was of spiral configuration extending to the diaphyseal region and emerging from an initial fissure. Specimen-specific factors favoring periprosthetic fracture were body mass index and varus angle of the implant. Periprosthetic fractures may extend to the subtrochanteric/diaphyseal region and may be of spiral configuration. According to the finding of this study, body mass index and varus/valgus position of the implant are important factors influencing the risk of periprosthetic fractures. Furthermore, partial weight-bearing as part of the postoperative regimen may be favorable.